Central Nervous System Lymphoma in a Patient with Chronic Lymphocytic Leukemia: A Case Report and Literature Review - Albakr, Abdulrahman (Cureus, 2018)
Chronic lymphocytic leukemia (CLL) is the most common type of leukemia that affects older adults in the Western world. Symptomatic nervous system invasion in undiagnosed CLL is rare, poorly understood, challenging to treat, and associated with decreased survival. The average survival of CLL patients with central nervous system (CNS) involvement is 3.79 years as compared to six years in CLL patients without CNS involvement. Autopsy studies demonstrated a high incidence of undiagnosed CLL with CNS involvement, suggesting that CNS involvement is either underdiagnosed or subclinical. Although the most common site of CNS involvement is the leptomeninges, our case demonstrates an extremely rare form of CNS diffuse large B-cell parenchymal involvement in a patient with a concurrent diagnosis of systemic CLL.